Multilevel Analysis: Villages do not have Ecological Effect on the Risk of Diabetes Mellitus Type 2 in Surakarta, Central Java - Anggi Putri Aria Gita; Isna Qadrijati; Bhisma Murti (Journal of Epidemiology and Public Health, 2020)
Background: Diabetes Melitus (DM) as The Silent Killer has an increasing number of cases. Type 2 diabetes and its complications are a major publ